Challenges Faced by Teachers and Students at Apayao State College When Using Modular Distance Learning Model: Basis for Intervention - Sanchez, Marfred T.; Tumaneng, Ruth A.; Espanol, Shane Pearl Lae S. (Current Progress in Arts and Social Studies Research Vol. 2, 2024)
The main objective of this study is to identify the problems encountered by the teachers and students in the implementation of modular distance learning modality in the BEEd Department of Apayao State College – Luna Campus, Philippines. Distance learning became the immediate response of academic institutions to sustain the learning continuity of the students. This learning delivery modality has different types that include online distance learning, TV or radio-based instruction, and modular distance learning. The study used a descriptive phenomenological approach to identify the problems encountered by teachers and students in implementing modular distance learning, as well as the possible solutions to the identified problems. The study was conducted among the teachers and students of the Bachelor of Elementary Education Department (BEEd) of Apayao State College – Luna Campus in the Philippines. Four (4) BEEd program mainstay teachers and ten (10) BEEd students were approached to request their voluntary involvement as key participants in the study. Data were analyzed using a thematic analysis approach to find any patterns in the participants’ responses by transcribing, organizing, and coding. Findings revealed four (4) themes of problems related to the preparation of printed learning materials; management in the distribution of printed learning materials; retrieval of students’ activities and outputs; and checking of students’ activities and outputs identified by teachers. Using digital technology to learn the lessons, such as recorded instructional videos and tutorial sites or links, may be beneficial. The quantity and level of difficulty of the activities to be given can be determined by considering the students' competency and ability to complete the tasks. Students also identified two (2) themes of problems they had in using modular distance learning that are related to the submission of their activities and outputs, as well as their capability to learn independently. School administrators can use the findings of this study to develop interventions, programs, and activities to address issues in the implementation of the modular distance learning modality. Schools may conduct relevant training, seminars, and workshops for teachers and students to upgrade their knowledge, skills, and competence in implementing modular distance learning modalities.